Multipartite dark matter with scalars, fermions and signatures at LHC - Subhaditya Bhattacharya; Purusottam Ghosh; Narendra Sahu (Journal of High Energy Physics, 2019)
Abstract Basic idea of this analysis is to achieve a two-component dark matter (DM) framework composed of a scalar and a fermion, with non-negligible DM-DM interaction contributing to thermal freeze out (hence relic density), but hiding them from direct detection bounds. We therefore augment the Standard Model (SM) with a scalar singlet (S) and three vectorlike fermions: two singlets (χ 1 , χ 2) and a doublet (N). Stability of the two DM components is achieved by a discrete Z 2 × Z 2 ′ $$ {\mathcal{Z}}_2 × {\mathcal{Z}}_2^{′ } $$ symmetry, under which the additional fields transform suitably. Fermion fields having same Z 2 × Z 2 ′ $$ {\mathcal{Z}}_2 × {\mathcal{Z}}_2^{′ } $$ charge (N, χ 1 in the model) mix after electroweak symmetry breaking (EWSB) and the lightest component becomes one of the DM candidates, while scalar singlet S is the other DM component connected to visible sector by Higgs portal coupling. The heavy fermion (χ 2) plays the role of mediator to connect the two DM candidates through Yukawa interaction. This opens up a large parameter space for the heavier DM component through DM-DM conversion. Hadronically quiet dilepton signature, arising from the fermion dark sector, can be observed at Large Hadron Collider (LHC) aided by the presence of a lighter scalar DM component, satisfying relic density and direct search bounds through DM-DM conversion.